Flame-retardant modified glass fiber reinforced flame-retardant PBT (polybutylene terephthalate) as well as preparation method and application thereof

By grafting the surface of the glass fiber without halogen-free flame retardant and combining specific formulas and processes, the problem of flammability of glass fiber reinforced polymer materials at high temperatures is solved, and the effect of suppressing the 'wick effect' and improving mechanical properties is achieved. Avoid environmental and health risks of flame retardants while reducing costs.

CN119144132APending Publication Date: 2024-12-17CHONGQING COPOLYFORCE NEW MATERIALS CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411372594.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing glass fiber reinforced polymer materials are flammable in high temperature environments, resulting in a 'wick effect', while the large amount of flame retardant is added to reduce mechanical properties, is harmful to the environment and health and increases costs, making it difficult to suppress flammability and maintain Find a balance between mechanical properties.

Method used

By modifying the surface of the glass fiber, the halogen-free flame retardant is grafted to form a bonded carbon layer, which improves compatibility with the polymer and interface bonding strength, and uses halogen-free flame retardant FR-A to use the glass to The fibers are modified and the flame-retardant modified glass fiber reinforced flame-retardant PBT is prepared in combination with specific formulas and processes.

Benefits of technology

Effectively suppress the 'wick effect', improve the flame retardant performance and mechanical properties, avoid the negative impact of flame retardant on the environment and health, and reduce material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144132A_ABST
    Figure CN119144132A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flame-retardant modified glass fibers, and discloses flame-retardant modified glass fiber reinforced flame-retardant PBT (polybutylene terephthalate) and a preparation method and application thereof.The flame-retardant modified glass fiber reinforced flame-retardant PBT is prepared from, by mass, 20-70 parts of PBT resin, 15-30 parts of GF-NH2-FR, 2-5 parts of polyphosphate, 5-10 parts of hypophosphite, 1-5 parts of flexibilizer, 0.1-1 part of flame-retardant synergist, 0.1-2 parts of nucleating agent, 0.1-2 parts of lubricant and 0.1-1 part of antioxidant. The GF-NH2-FR is glass fiber modified by using a flame retardant, namely, hydroquinone modified phenyl phosphoryl dichloride. According to the flame-retardant PBT material disclosed by the invention, the mechanical property of the material is ensured while the candlewick effect of the material is inhibited by integrally optimizing the composition and the preparation process of the flame-retardant PBT material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant modified glass fibers, and in particular to flame retardant modified glass fiber reinforced flame retardant PBT and a preparation method and application thereof. Background Art

[0002] Glass fiber (GF), as an inorganic non-metallic material, is well-known for its excellent mechanical strength, excellent heat resistance, chemical resistance and good insulation properties. These properties make glass fiber an ideal choice for polymer reinforcement and can significantly improve the mechanical properties of polymer composites. Therefore, glass fiber is widely used in many fields such as construction, electronics, transportation, aerospace, and national defense, demonstrating its important value in industrial production and daily life.

[0003] Polymer materials are flammable because they contain a large amount of hydrocarbon elements. When polymers are compounded with glass fibers, although the mechanical properties are significantly improved, under high temperature conditions, the polymer melt will infiltrate the surface of the glass fiber and generate interfacial tension. This phenomenon is called the "wick effect". Specifically, the "wick effect" refers to the rapid infiltration, spread and flow of the polymer melt through the surface of the glass fiber to the combustion area, further exacerbating the fire hazard of polymer composites. Therefore, polymer composites with added glass fibers face huge challenges in flame retardant modification, and their development and application are therefore restricted.

[0004] In order to reduce the flammability of glass fiber reinforced polymer materials, the current common solution is to compound or add a large amount of flame retardants to polymer / GF composite materials to suppress the "wick effect". However, this method has obvious limitations:

[0005] 1. Decreased mechanical properties: The addition of a large amount of flame retardants often leads to a serious decrease in the mechanical properties of glass fiber reinforced polymer materials, which inhibits the gain effect brought by glass fiber. This is a major problem for those application fields that have strict requirements on mechanical properties.

[0006] 2. Environmental issues: Some flame retardants may release harmful substances at high temperatures, causing adverse effects on human health and the environment.

[0007] 3. Cost issue: Adding a large amount of flame retardants will increase the cost of the material, affecting its economy and market competitiveness.

[0008] Therefore, it is of great significance to modify the glass fiber to improve its mechanical properties while suppressing the "wick effect". Summary of the invention

[0009] The present invention aims to provide a flame retardant modified glass fiber reinforced flame retardant PBT and a preparation method and application thereof, which can suppress the "wick effect" of the material while ensuring the mechanical properties of the material.

[0010] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a flame retardant modified glass fiber reinforced flame retardant PBT, which comprises, by mass, 20 to 70 parts of PBT resin, 15 to 30 parts of GF-NH2-FR, 2 to 5 parts of polyphosphate, 5 to 10 parts of hypophosphite, 1 to 5 parts of toughening agent, 0.1 to 1 part of flame retardant synergist, 0.1 to 2 parts of nucleating agent, 0.1 to 2 parts of lubricant, and 0.1 to 1 part of antioxidant, wherein GF-NH2-FR is a glass fiber modified by phenylphosphinoyl dichloride modified with flame retardant hydroquinone.

[0011] Preferably, as an improvement, the amount of the flame retardant added to GF-NH2-FR is 10-15%.

[0012] Preferably, as an improvement, the PBT resin is at least one of PBT-KH2100, PBT-GX121 (L2100), PBT-TH6100, and PBT-KH2130, and the melting index of the PBT resin is 0.1-100.

[0013] Preferably, as an improvement, the PBT resin is compounded by PBT-KH2100 and PBT-TH6100 in a mass ratio of 30-40:20-30.

[0014] Preferably, as an improvement, the polyphosphate is melamine polyphosphate, and the 1% thermal weight loss is ≥ 330°C; and the hypophosphite is diethyl aluminum hypophosphite.

[0015] Preferably, as an improvement, the toughening agent is an ethylene copolymer toughening agent; the flame retardant synergist is at least one of anhydrous zinc borate, zinc sulfide, anhydrous zinc borate, and phosphite; the nucleating agent is a crystalline nucleating agent; the lubricant is at least one of pentaerythritol stearate, white oil, silicone oil, polyethylene wax, silicone and amide wax; and the antioxidant is antioxidant 168, antioxidant 1010 or antioxidant 1098.

[0016] Preferably, as an improvement, the preparation method of GF-NH2-FR comprises the following steps:

[0017] S1, phenylphosphoryl dichloride undergoes substitution reaction to obtain hydroquinone-modified phenylphosphoryl dichloride FR-A;

[0018] S2. Amino modification of glass fiber: disperse glass fiber GF in ethanol / water, add amino coupling agent under high-speed stirring, and after the temperature reaction is completed, filter, wash and dry to obtain GF-NH2;

[0019] S3. Preparation of flame-retardant modified glass fiber: GF-NH2 is dispersed in a solvent, FR-A is added to the solution for reaction, and then diamine dispersed in ethanol is added dropwise to the mixed solution for further reaction. After the reaction is completed, GF-NH2-FR is obtained by filtering, washing and drying.

[0020] Preferably, as an improvement, a flame retardant modified glass fiber reinforced flame retardant PBT includes, by mass, 30 to 40 parts of PBT-KH2100, 20 to 30 parts of PBT-TH6100, 15 to 30 parts of GF-NH2-FR, 2 to 5 parts of melamine polyphosphate, 5 to 10 parts of diethyl aluminum hypophosphite, 1 to 3 parts of M-701, 0.1 to 2 parts of anhydrous zinc borate, 0.1 to 1 part of nucleating agent P250, 0.1 to 1 part of lubricant pentaerythritol stearate, 0.1 to 1 part of antioxidant 168, and 0.1 to 1 part of antioxidant 1010.

[0021] Preferably, as an improvement, a method for preparing flame retardant modified glass fiber reinforced flame retardant PBT comprises the following steps:

[0022] Step 1: Add polyphosphate, hypophosphite and flame retardant synergist into a high-speed mixer and stir at room temperature for 5 to 30 minutes;

[0023] Step 2: Add PBT resin, lubricant and antioxidant to the mixture of step 1 and stir for 5 to 30 minutes;

[0024] The mixture of step 3 and step 2 is extruded by a twin-screw extruder at a temperature of 200-260° C. GF-NH2-FR is fed into the twin-screw extruder through side feeding, and then through the processes of drawing and pelletizing, screening and dehydration to obtain flame-retardant reinforced PBT granules.

[0025] Preferably, as an improvement, in step three, the main screw speed is 120r / min and the feeding frequency is 10Hz.

[0026] The principle and advantage of this solution are: in practical application, in this technical solution, in view of the problem that the "wick effect" and mechanical properties of GF reinforced polymer materials in the prior art cannot be taken into account, the present invention modifies the surface of glass fiber and grafts the organic flame retardant on the surface of glass fiber, so that at high temperature, the GF composite material forms a bonding carbon layer on the GF surface, increases its surface roughness, and improves the compatibility of glass fiber and flame retardant terephthalate. Thereby achieving the effect of suppressing the "wick effect" while increasing the bonding strength of the interface between GF / composite matrix, further enhancing the flame retardant performance of the system. In the technical research and development stage, the structural design of flame retardant modified glass fiber is one of the difficulties of this technical solution. It is necessary to tightly graft the flame retardant to the surface of glass fiber while suppressing the "wick effect", and at the same time, it is necessary to ensure the subsequent compatibility with PET. In addition, in the field, conventional glass fiber modified reinforced PBT materials are to treat the glass fiber with amino, and the method adopted in this solution is to graft the halogen-free flame retardant FR-A to the surface of amino glass fiber for the first time, overcoming the technical prejudice in the field.

[0027] In summary, the beneficial effects of this technical solution are:

[0028] 1. This technical solution eliminates or suppresses the "wick effect" and enhances flame retardancy by surface modification of GF;

[0029] 2. After the GF surface of this technical solution is modified with a halogen-free flame retardant with a certain molecular chain, the compatibility of glass fiber and flame-retardant PBT can be improved; FR-A modified glass fiber is used for the first time, and the structure (connection method) of FR-A + glass fiber is optimized;

[0030] 3. The halogen-free flame retardant in this technical solution has an excellent carbonization effect. It can self-crosslink to form carbon at a relatively low temperature and pyrolyze small molecules of polymer materials at high temperature to form a carbon layer with high thermal stability. It has a good "wick effect" suppression effect and can further enhance the flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a physical picture of the flame retardant modified glass fiber reinforced PBT composite material in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0033] Program Overview:

[0034] A flame retardant modified glass fiber reinforced flame retardant PBT comprises, by weight, 20-70 parts of PBT resin, 15-30 parts of GF-NH2-FR, 2-5 parts of polyphosphate, 5-10 parts of hypophosphite, 1-5 parts of toughening agent, 0.1-1 part of flame retardant synergist, 0.1-2 parts of nucleating agent, 0.1-2 parts of lubricant and 0.1-1 part of antioxidant.

[0035] The PBT resin is at least one of PBT-KH2100, PBT-GX121 (L2100), PBT-TH6100 and PBT-KH2130, and the melting index of the PBT resin is 0.1-100. In this embodiment, the PBT resin is preferably compounded with 30 to 40 parts of PBT-KH2100 and 20 to 30 parts of PBT-TH6100.

[0036] The preparation method of GF-NH2-FR (flame retardant modified glass fiber) comprises the following steps:

[0037] S1, phenylphosphoryl dichloride is subjected to substitution reaction to obtain hydroquinone-modified phenylphosphoryl dichloride

[0038] The specific operation is as follows: hydroquinone and phenylphosphoryl dichloride are added to a three-necked flask containing dioxane in a molar ratio of 1:3, and the mixture is condensed and refluxed at 70°C with magnetic stirring for 8 hours under nitrogen protection. The stirring speed is 850 r / min, and the product is washed with ice water for 3 times and vacuum dried for 24 hours to obtain FR-A. The reaction formula is shown in formula (I):

[0039]

[0040] S2. Amino modification of glass fiber

[0041] The chopped yarn 303CL (GF) was dispersed in ethanol / water, and an amino coupling agent was added under high-speed stirring. The temperature was raised from room temperature to 60-100°C for reaction for 4-8 hours. After the reaction was completed, GF-NH2 was obtained by filtration, washing, and drying at 80°C. The structural formula of the obtained GF-NH2 is shown in formula (II):

[0042]

[0043] S3. Preparation of flame retardant modified glass fiber

[0044] GF-NH2 is dispersed in a solvent (ethanol, water, DMF, DMSO, acetonitrile and other organic solvents), uniformly dispersed in ethanol, FR-A is added to the solution, and the reaction is continued at 1-50°C for 2-8h, and then the diamine dispersed in ethanol is added dropwise to the mixed solution at 1-50°C for 2-4h. After the reaction is completed, GF-NH2-FR is obtained by filtering, washing and drying at 80°C. The structural formula is shown in formula (III):

[0045]

[0046] The polyphosphate is melamine polyphosphate (MPP), and the 1% thermal weight loss is ≥330°C.

[0047] The hypophosphite was diethylaluminum hypophosphite (ADP).

[0048] The toughening agent is an ethylene copolymer toughening agent, specifically at least one of methyl methacrylate-butadiene-styrene (MBS) toughening agents M-701 and M-722, ethylene methacrylate (MMA) toughening agent AX8900, and ethylene-ethyl acrylate (EEA) toughening agent 4700.

[0049] The flame retardant synergist is at least one of anhydrous zinc borate, zinc sulfide, anhydrous zinc borate and phosphite.

[0050] The nucleating agent is a crystal nucleating agent, specifically at least one of P22, P250, and P252.

[0051] The lubricant is at least one of pentaerythritol stearate, white oil, silicone oil, polyethylene wax, silicone and amide wax.

[0052] The antioxidant is antioxidant 168, antioxidant 1010 or antioxidant 1098.

[0053] A method for preparing flame-retardant modified glass fiber reinforced flame-retardant PBT comprises the following steps:

[0054] Step 1: Add polyphosphate, hypophosphite and flame retardant synergist into a high-speed mixer and stir at room temperature for 5 to 30 minutes;

[0055] Step 2: Add PBT resin, lubricant and antioxidant to the mixture of step 1 and stir for 5 to 30 minutes;

[0056] The mixture of step 3 and step 2 is extruded by a twin-screw extruder at a temperature of 200-260°C. GF-NH2-FR is fed into the twin-screw extruder through side feeding, and then through the process of drawing and pelletizing, sieving and dehydrating to obtain flame-retardant reinforced PBT granules. Among them, the temperatures of each section of the extruder are 230±10, 240±10, 240±10, 245±10, 245±10, 245±10, 245±10, 240±10, 240±10°C, the main screw speed is 120r / min, and the feeding frequency is 10Hz.

[0057] Example 1

[0058] A flame retardant modified glass fiber reinforced flame retardant PBT, which comprises, by mass, 32 parts of PBT-TH2100, 20 parts of PBT-TH6100, 30 parts of GF-NH2-FR, 10 parts of diethyl aluminum hypophosphite (ADP), 5 parts of melamine polyphosphate (MPP), 1.5 parts of toughening agent M-701, 0.5 parts of anhydrous zinc borate, 0.3 parts of pentaerythritol stearate (PETS), 0.2 parts of nucleating agent P250, 0.2 parts of antioxidant 1010 and 0.3 parts of antioxidant 168.

[0059] A method for preparing flame retardant modified glass fiber reinforced flame retardant PBT comprises the following steps:

[0060] Step 1: Add melamine polyphosphate (MPP), diethyl aluminum hypophosphite (ADP), and anhydrous zinc borate into a high-speed mixer at room temperature and stir for 10 to 40 minutes;

[0061] Step 2: Add PBT-KH2100, PBT-TH6100, M-701, P250, pentaerythritol stearate (PETS), antioxidants 168 and 1010 to the mixture of step 1 and stir for 10 to 40 minutes;

[0062] Step 3, the mixture of step 2 is extruded through a twin-screw extruder at a temperature of 220-260°C, GF-NH2-FR is fed into the twin-screw extruder through side feeding, and then through the processes of drawing and pelletizing, screening and dehydration to obtain flame retardant reinforced PBT granules, wherein the temperatures of each section of the extruder are 230±10, 240±10, 240±10, 245±10, 245±10, 245±10, 245±10, 240±10, 240±10°C, respectively, the main screw speed is 120r / min, and the feeding frequency is 10Hz.

[0063] The preparation method of GF-NH2-FR comprises the following steps:

[0064] S1. First, FR-A (same as the general description of the scheme) is prepared by stirring and reacting hydroquinone with phenylphosphoryl dichloride.

[0065] S2. Disperse GF (100 g) in ethanol / water (500 ml, 450:50), add 1 wt% (1 g) of amino coupling agent KH550 under high-speed stirring, raise the temperature from room temperature to 80-100°C, and after the reaction is completed, filter, wash and dry at 80°C to obtain GF-NH2.

[0066] S3. GF-NH2 (100 g) was evenly dispersed in ethanol (500 ml, 400:100), FR-A (1 g) was added to the solution, and the reaction was continued at 50°C for 6 h. After the reaction, ethylenediamine dispersed in ethanol was added dropwise to the solution, and the reaction was continued at 50°C for 2 h. After the reaction was completed, GF-NH2-FR was obtained by filtering, washing, and drying at 80°C.

[0067] Example 2

[0068] The difference between this embodiment and embodiment 1 is that: in this embodiment, when the glass fiber is treated with a halogen-free flame retardant, the addition amount of the flame retardant is 12% (15% in embodiment 1), and a flame retardant modified glass fiber reinforced flame retardant PBT, in parts by mass, includes 34 parts of PBT-TH2100, 21 parts of PBT-TH6100, 30 parts of GF-NH2-FR, 8 parts of diethyl aluminum hypophosphite (ADP), 4 parts of melamine polyphosphate (MPP), 1.5 parts of toughening agent M-701, 0.5 parts of anhydrous zinc borate, 0.3 parts of pentaerythritol stearate (PETS), 0.2 parts of nucleating agent P250, 0.2 parts of antioxidant 1010, and 0.3 parts of antioxidant 168.

[0069] Example 3

[0070] The difference between this embodiment and embodiment 1 is that: in this embodiment, when the glass fiber is treated with a halogen-free flame retardant, the addition amount of the flame retardant is 10% (15% in embodiment 1), and a flame retardant modified glass fiber reinforced flame retardant PBT, in parts by mass, 35 parts of PBT-TH2100, 22 parts of PBT-TH6100, 30 parts of GF-NH2-FR, 6.7 parts of diethyl aluminum hypophosphite (ADP), 3.3 parts of melamine polyphosphate (MPP), 1.5 parts of toughening agent M-701, 0.5 parts of anhydrous zinc borate, 0.3 parts of pentaerythritol stearate (PETS), 0.2 parts of nucleating agent P250, 0.2 parts of antioxidant 1010, and 0.3 parts of antioxidant 168.

[0071] Comparative Example 1 (GF without treatment, flame retardant added 15%)

[0072] The difference between this comparative example and Example 1 is that in this comparative example, short-cut GF without any treatment is used to replace GF-NH2-FR.

[0073] Comparative Example 2 (GF without treatment, flame retardant added 12%)

[0074] The difference between this comparative example and Example 2 is that in this comparative example, short-cut GF without any treatment is used to replace GF-NH2-FR.

[0075] Comparative Example 3 (GF without treatment, flame retardant added 10%)

[0076] The difference between this comparative example and Example 3 is that in this comparative example, short-cut GF without any treatment is used to replace GF-NH2-FR.

[0077] Comparative Example 4 (GF treated with coupling agent only, flame retardant added 15%)

[0078] The difference between this comparative example and Example 1 is that in this comparative example, GF-NH2 is prepared by dispersing 100g of short-cut GF in ethanol / water (500ml, 450:50), adding 1wt% (1g) of amino coupling agent KH550 under high-speed stirring, and reacting from room temperature to 90°C for 6h. After the reaction is completed, GF-NH2 is obtained by filtering, washing and drying at 80°C.

[0079] Comparative Example 5 (GF treated with coupling agent only, flame retardant added 12%)

[0080] The difference between this comparative example and Example 2 is that in this comparative example, GF-NH2 is prepared by dispersing 100g of short-cut GF in ethanol / water (500ml, 450:50), adding 1wt% (1g) of amino coupling agent KH550 under high-speed stirring, and reacting from room temperature to 90°C for 6h. After the reaction is completed, GF-NH2 is obtained by filtering, washing and drying at 80°C.

[0081] Comparative Example 6 (GF treated with coupling agent only, flame retardant added 10%)

[0082] The difference between this comparative example and Example 3 is that in this comparative example, GF-NH2 is prepared by dispersing 100g of short-cut GF in ethanol / water (500ml, 450:50), adding 1wt% (1g) of amino coupling agent KH550 under high-speed stirring, and reacting from room temperature to 90°C for 6h. After the reaction is completed, GF-NH2 is obtained by filtering, washing and drying at 80°C.

[0083] Comparative Example 7 (GF treated with ADP, flame retardant added 10%)

[0084] The difference between this comparative example and Example 1 is that in this comparative example, the flame retardant diethylphosphite (ADP) is used when modifying GF. The specific operation is to evenly disperse GF-NH2 (100g) in ethanol (500ml, 400:100), add ADP (1g) into the solution, and continue to react at 50°C for 6h. After the reaction, ethylenediamine dispersed in ethanol is added dropwise into the solution, and the reaction is continued at 50°C for 2h. After the reaction is completed, GF-NH2-ADP is obtained by filtering, washing, and drying at 80°C.

[0085] Comparative Example 8 (GF treated with MPP, flame retardant added 10%)

[0086] The difference between this comparative example and Example 1 is that in this comparative example, when modifying GF, the flame retardant melamine polyphosphate (MPP) is used, and the specific operation is to evenly disperse GF-NH2 (100g) in ethanol (500ml, 400:100), add MPP (1g) into the solution, and continue to react at 50°C for 6h. After the reaction, ethylenediamine dispersed in ethanol is added dropwise into the solution, and the reaction is continued at 50°C for 2h. After the reaction is completed, GF-NH2-MPP is obtained by filtering, washing, and drying at 80°C.

[0087] For the convenience of comparison, the formulas of the composite PBT materials of Examples 1 to 3 and Comparative Examples 1 to 6 are summarized as shown in Table 1:

[0088] Table 1

[0089]

[0090]

[0091] Experimental Example 1 Performance Test

[0092] The flame retardant properties and mechanical properties of the composite PBT materials prepared in the above embodiments and comparative examples are tested. The specific method is as follows: the composite PBT materials prepared in the above embodiments and comparative examples are used as raw materials, and after the raw materials are dried, they are mixed evenly with a high mixer, and then melt-extruded and granulated with a screw extruder. The obtained pellets are dried at 80°C for 12 hours and then injection molded with an injection molding machine to obtain test samples. The temperatures of each section of the extruder are 220±10, 240±10, 250±10, 250±10, 260±10, 260±10, 250±10, 250±10, 240±10°C, respectively. The speed of the main screw is 120r / min, and the feeding frequency is 10Hz. Among them, the actual picture of the flame-retardant reinforced PET composite material prepared in Example 1 is as shown in the figure. Figure 1 shown.

[0093] The flame retardant performance test method is carried out in accordance with GB / T 2408-2008 and ASTM D2863;

[0094] The mechanical properties testing method is carried out with reference to GB / T 1040.1-2018 and GB / T 1843-2008.

[0095] The test results are shown in Table 2. From the data in Table 2, it can be seen that the mechanical properties will be reduced when the flame retardant is compounded or added in large quantities; Comparative Examples 1-3 are the performance conditions after the addition of traditional glass fibers. The results show that the mechanical properties are slightly lower than the levels of Examples 1-3, but the flame retardant properties are inferior to the levels of Examples 1 to 3 of this solution. In addition, the selection of flame retardants has a great influence on the mechanical properties and flame retardant properties of the material. Although flame retardants are used in Comparative Examples 7-8 to modify the glass fibers, their mechanical properties and flame retardancy are significantly lower than those of Example 3 of the present invention, indicating that only the present technical solution using FR-A for grafting modification of glass fibers can achieve the expected effect.

[0096]

[0097]

[0098] Table 2

[0099] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A flame retardant modified glass fiber reinforced flame retardant PBT, characterized in that: The invention comprises, by weight, 20 to 70 parts of PBT resin, 15 to 30 parts of GF-NH2-FR, 2 to 5 parts of polyphosphate, 5 to 10 parts of hypophosphite, 1 to 5 parts of toughening agent, 0.1 to 1 part of flame retardant synergist, 0.1 to 2 parts of nucleating agent, 0.1 to 2 parts of lubricant and 0.1 to 1 part of antioxidant. The GF-NH2-FR is a glass fiber modified with phenylphosphinoyl dichloride modified with the flame retardant hydroquinone.

2. The flame retardant modified glass fiber reinforced flame retardant PBT according to claim 1, characterized in that: In the GF-NH2-FR, the added amount of the flame retardant is 10-15%.

3. The flame retardant modified glass fiber reinforced flame retardant PBT according to claim 2, characterized in that: The PBT resin is at least one of PBT-KH2100, PBT-GX121 (L2100), PBT-TH6100 and PBT-KH2130, and the melting index of the PBT resin is 0.1-100.

4. The flame retardant modified glass fiber reinforced flame retardant PBT according to claim 3, characterized in that: The PBT resin is compounded by mixing PBT-KH2100 and PBT-TH6100 in a mass ratio of 30-40:20-30.

5. The flame retardant modified glass fiber reinforced flame retardant PBT according to claim 4, characterized in that: The polyphosphate is melamine polyphosphate, and the 1% thermal weight loss is ≥330°C; the hypophosphite is diethyl aluminum hypophosphite.

6. The flame retardant modified glass fiber reinforced flame retardant PBT according to claim 5, characterized in that: The toughening agent is an ethylene copolymer toughening agent; the flame retardant synergist is at least one of anhydrous zinc borate, zinc sulfide, anhydrous zinc borate, and phosphite; the nucleating agent is a crystalline nucleating agent; the lubricant is at least one of pentaerythritol stearate, white oil, silicone oil, polyethylene wax, silicone and amide wax; the antioxidant is antioxidant 168, antioxidant 1010 or antioxidant 1098.

7. The flame retardant modified glass fiber reinforced flame retardant PBT according to claim 6, characterized in that: The preparation method of GF-NH2-FR comprises the following steps: S1, phenylphosphoryl dichloride undergoes substitution reaction to obtain hydroquinone-modified phenylphosphoryl dichloride FR-A; S2. Amino modification of glass fiber: disperse glass fiber GF in ethanol / water, add amino coupling agent under high-speed stirring, and after the temperature reaction is completed, filter, wash and dry to obtain GF-NH2; S3. Preparation of flame-retardant modified glass fiber: GF-NH2 is dispersed in a solvent, FR-A is added to the solution for reaction, and then diamine dispersed in ethanol is added dropwise to the mixed solution for further reaction. After the reaction is completed, GF-NH2-FR is obtained by filtering, washing and drying.

8. The flame retardant modified glass fiber reinforced flame retardant PBT according to claim 7, characterized in that: Calculated by mass, it includes 30 to 40 parts of PBT-KH2100, 20 to 30 parts of PBT-TH6100, 15 to 30 parts of GF-NH2-FR, 2 to 5 parts of melamine polyphosphate, 5 to 10 parts of diethyl aluminum hypophosphite, 1 to 3 parts of M-701, 0.1 to 2 parts of anhydrous zinc borate, 0.1 to 1 part of nucleating agent P250, 0.1 to 1 part of lubricant pentaerythritol stearate, 0.1 to 1 part of antioxidant 168, and 0.1 to 1 part of antioxidant 1010.

9. The method for preparing flame-retardant modified glass fiber reinforced flame-retardant PBT according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Add polyphosphate, hypophosphite and flame retardant synergist into a high-speed mixer and stir at room temperature for 5 to 30 minutes; Step 2: Add PBT resin, lubricant and antioxidant to the mixture of step 1 and stir for 5 to 30 minutes; The mixture of step 3 and step 2 is extruded by a twin-screw extruder at a temperature of 200-260° C. GF-NH2-FR is fed into the twin-screw extruder through side feeding, and then through the processes of drawing and pelletizing, screening and dehydration to obtain flame-retardant reinforced PBT granules.

10. The method for preparing flame-retardant modified glass fiber reinforced flame-retardant PBT according to claim 9, characterized in that: In step 3, the main screw speed is 120r / min and the feeding frequency is 10Hz.

Citation Information

Cited By

  • PBT (polybutylene terephthalate) modified material as well as preparation method and application thereof

    CN119752127A

  • A pbt modified material, its preparation method and application

    CN119752127B